1997
DOI: 10.1159/000106659
|View full text |Cite
|
Sign up to set email alerts
|

<i>Borrelia burgdorferi</i>-Seropositive Chronic Encephalomyelopathy: Lyme Neuroborreliosis?

Abstract: A 36-year-old Japanese woman presented with progressive cerebellar signs and mental deterioration of subacute course after her return from the USA. Her serum antibody to spirochete Borrelia burgdorferi was significantly elevated. A necropsy 4 years after her initial neurological signs revealed multifocal inflammatory change in the cerebral cortex, thalamus, superior colliculus, dentate nucleus, inferior olivary nucleus and spinal cord. The lesions showed spongiform change, neuronal cell loss, astrocytosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…The combination of OMS and neuroborreliosis has been reported previously, in a child [5] and in an autopsy study [6]. In both our patients and the child, only IgM antibodies in CSF were detected.…”
Section: Discussionsupporting
confidence: 81%
“…The combination of OMS and neuroborreliosis has been reported previously, in a child [5] and in an autopsy study [6]. In both our patients and the child, only IgM antibodies in CSF were detected.…”
Section: Discussionsupporting
confidence: 81%
“…In our case, the MRI showed a tenuous and unspecific thalamic hyper-signal in T2-weighted and FLAIR sequences. Even though the same findings had been described in one idiopathic case by Bataller et al,15 Kobayashi et al33 found thalamic lesions in the autopsy of a Borrelia burgdorferi -seropositive chronic encephalomyelopathy. Furthermore, blood and CSF tests are most useful in diagnosing an infection, but do not confirm or exclude a paraneoplastic or autoimmune etiology.…”
Section: Discussionsupporting
confidence: 65%
“…The most common manifestations of Lyme neuroborreliosis are headache, meningismus, or radiculopathic symptoms, whereas CNS parenchymal involvement is rare (Hansen and Lebech, 1992;Pacher et al, 1998a). The localization of spirochetes in the CNS of humans has been reported only in a handful of cases using nonspecific silver impregnation techniques (Kobayashi et al, 1997;Kuntzer et al, 1991;Miklossy et al, 1990). The positivity of the PCR-ELISA in samples from the cerebrum and brainstem likely represents leptomeningeal, rather than parenchymal, localization.…”
Section: Borrelia Burgdorferi In Immunosuppressed Macaca Mulattamentioning
confidence: 99%